SUSTAINED POTENTIATION OF < ALPHA > 1-ADRENERGIC VASOCONSTRICTION BY SPHINGOSINE 1-PHOSPHATE. (June 2018) - Panta, C.R.; Ruisanchez, É.; Móré, D.; Dancs, P.; Balogh, A.; Offermanns, S.; Tigyi, G.; Benyó, Z.
Abstract : Objective: In our present project we aimed to examine the vasoactive effects of sphingosine 1-phosphate (S1P) by evaluating its capability to alter the basal vascular tone and to influence vasoconstriction mediated by α1-adrenoreceptors Design and method: Effects of S1P and the α1–adrenoreceptor agonist phenylephrine (PE) on the tone of the mouse thoracic aorta have been determined under isometric conditions with myography. Responses of vessels isolated from wild type (WT), S1P1, S1P2, and S1P3 receptor-, or G12/13-KO mice were measured and tone changes were normalized to vasoconstriction induced by 124 mM K+. Results: Addition of 5 μM S1P, which is in the concentration range reported in the human serum, did not cause significant change in the resting vascular tone. In contrast, EC50 of the vasoconstrictor effect of PE decreased, whereas Emax increased following 20 min incubation with 5 μM S1P in WT vessels, indicating a marked potentiating effect. Similar enhancement of the vascular reactivity was detected in S1P1- and S1P3-KO segments. In S1P2-KO vessels, however, this phenomenon was absent. In addition, the potentiating effect of S1P was also lacking in vessels of G12/13-KO mice and after inhibition of the Rho-kinase by Y27632 in WT vessels. In further experiments we aimed to evaluate the duration of the S1P-induced enhancement of α1-adrenoreceptor-mediated vasoconstriction. Therefore, contractions evoked by 100 nM PE determined every 20 minutes, repeatedly, following a 20-min incubation with S1P. Reactivity remained enhanced for 3 hours in WT segments, whereas this increase could not be detected in S1P2-KO vessels. Conclusions: Although S1P does not modify directly the resting vascular tone by itself, yet it significantly enhances α1-adrenoreceptor-mediated vasoconstriction even at three hours after exposure. The S1P2 receptor/G12/13 / Rho-kinase pathway appears to be responsible for this potentiating effect of S1P. The sustained enhancement of vascular reactivity detected underlines the potential patophysiological significance of this phenomenon in diseases associated with enhanced S1P production.